(untitled) (Linguostylistic Studies, 2021)
The article elucidates the study findings regarding the specific functioning features of a Compound Nominal Predicate in legal languge style. A case study material is the Constitution of the Republic of Poland. In the process of lingual-stylistic analysis of Сompound Nominal Predicates identified in the document, it was found out that a Compound Predicate is quite productive in this style. In the focus of analysis are the lexico-grammatical means of expressing predicatives. Being a frequent occurrence in business language, this category has both general features of functioning, characteristic for all predicates, and specific ones, characteristic only of a Compound Nominal Predicate. The linking verb types in the above-mentioned syntactic category in the sentences from the text of the Constitution of the Republic of Poland are not diverse. 90% of constructions have a predicate with a linking verb być in different tenses and forms (most often in the Present tense of Indicative Mood of the third person singular or plural). From a morphological point of view, the predicative element is most productively expressed by nouns in the Common Case and an adjective or Participle form in the Common Case. To express a predicative feature, the text of the Basic Law of Poland actively uses a polynomial compound predicate, which, due to its specific organization, is characterized by multifunctional capacity and causes some difficulty in expressing lexical and grammatical meanings, productively conveys the semantics of the objective modality, which determines the reality or unreality of the sentence content. Despite a high frequency of operation, this syntactic category is not particularly diverse. Thus, the first component of the linking part of the predicate, the modal auxiliary verb, is almost in 100% cases represented by the word móc in the form of the Present tense of the third person singular, its second component is expressed by the infinitive być, but the predicate nominative part is mostly expressed by Participle in the form of a noun, much less often – by a noun in the instrumental case. The business style is characterized by the use of stable formulas that serve as the nominative part of the Compound Nominal Predicate and are a combination of two or more words between which there are semantic and grammatical connections. Lexically structural components are so interconnected that they express a single concept. The case study of the text of the Constitution of the Republic of Poland has revealed that, although the organization of a predicate is not characterized by a diversity of structure, the method of expressing a predicative feature in syntactic constructions with the help of a Compound Nominal Predicate is rather productive, demonstrating the highest frequency of using Participle, Nominative and Adjectives in the predicative part.